Dentists´ and Dental Hygienists´ experiences of the Capitation Contract System-the dilemma of conflicting loyalties - Emelie Boberg; Bengt Franzon; Annsofi Johannsen (Nature Publishing Group, 2022)
Abstract Objective The Capitation Contract system (CCS) is a payment model adopted by the Swedish Public Dental Health Service (PDHS). Patients enrolled in the CCS are usually assessed as being at lower risk of dental disease and are more regular dental attenders than those treated by Fee for Service (FFS). With increasing numbers of patients and CCS enrolments, Sweden faces a shortage of dental personnel. Our aim was to analyse dentists´ and dental hygienists´ perceptions and experiences of the capitation contact system. Material and methods Eleven dentists and dental hygienists from three Swedish regions participated in online qualitative interviews conducted according to the Grounded Theory methodology. Results When working with CCS the informants tried hard ´to find a balance between attitudes, compliance with guidelines and clinical resources´. Not all patients were offered CCS, even though they qualified: among other determinants were the informants' interpretations of guidelines and regulations, clinical resources, and patient interest. Conclusions When dental resources are in balance, the informants appreciate the CCS and consider it to be favourable to patient health but are aware of conflicting loyalties of their dual roles of insurance sales agent and care provider. The informants´ individual mindset affects which patients are offered CCS enrolment.